Assessing the physico-mechanical properties of precast papercrete as construction material on the addition of bottom ash as lightweight aggregate - Matanguihan, Jacobsen D.; Cartajenas, Alexis Ken S. (2016)
One concept of sustainability includes the utilization of available energy resources and the reuse of waste materials from other processes to produce simple, energy efficient building alternatives, and to develop new techniques to satisfy the increasing demand in the building industry. The research study reports on the results of the utilization of waste materials such as wastepaper and coal bottom ash on the material development of Precast Papercrete (PP), identifying the best mix ratio, and the investigation of its physical properties as a possible new building material that can be practiced in the local construction industry. There were three mix ratios of cement- coal bottom ash-wastepaper pulp according to volume, namely: PP1, PP2, and PP3. The precast papercrete samples that were created per mix ratio were subjected to several tests; compressive strength test, water absorptivity test, and fire resistivity test. Weight loss per sample and shrinkage during the curing time were also documented. After results of the tests were analyzed, it showed all the samples were non-flammable under one hour exposure to fire, but PP1 had the highest results in the compressive strength test and had the slowest rate of water absorption. Overall, the results revealed that PP1 proved to have a potential to be used as a building material. The proposed building material was a precast papercrete panel that utilizes the tilt-up wall system as its installation methods.
Thesis (BS Architecture) -- University of the Philippines Mindanao, June 2016.